Gamification in Education: A Literature Review - Φελεκίδου Κρυσταλία; Λενακάκης Αντώνης (Education Sciences, 2022)
The article is an integrative literature review in the field of gamification in education, based on Torraco’s (2016) criteria. It aims to deconstruct and recompose the concept of gamification, highlighting its theoretical, psychological and pedagogical principles, that classify gamification as an upcoming educational tool. First of all, the definition of gamification is discussed, as well as its importance as an educational innovation. Furthermore, the role of gamification in reinforcing motivation is emphasized, through an analysis of its elements that seem to affect students’ motivation. Finally, there is a presentation of research conclusions regarding the effectiveness of gamification in educational context, and suggestions for further research are made.